Pengaruh Penambahan Kelakai (Stenochlaena Palustris) Terhadap Sifat Fisikkokimia Bakso Daging Ayam Ras - Dwijayanti, Ratumas Sherly; Astuti, Maria H.; Ma’rifah, Siti (Unpad Press, 2023)
ABSTRAKMeatballs are processed products from meat, which are consumed by Indonesian people. Common ingredients in meatball dough are flour, salt, water and other seasonings. Meatballs contain energy, protein, carbohydrates, fat, calcium, and iron. This research was conducted to determine the effect of the addition kelakai on the yield, cooking loss, water content, protein and fat content of purebred chicken meatballs. This research was conducted at the Laboratory of Animal Husbandry Study Program, University of Palangka Raya. This study used an experimental method with a completely randomized design (CRD), there were 4 treatments and 4 replications, namely P1 (Making Meatballs 100% chicken meat + 0% fish meatballs), P2 (Making Meatballs 97.5% chicken meat + 2.5% fish meatballs), P3 (Making Meatballs 95% chicken meat + 5% kelakai), P4 (Making meatballs 92.5% chicken meat + 7.5% kelakai). The variables observed in this study were yield content, cooking loss, water content, protein and fat content. The data were analyzed using a test of variance and if it had a significant effect followed by using Duncan's multiple range test. From the results of the analysis of variance, it was shown that the addition kelakai in chicken meatballs had a significant effect on the protein content of chicken meatballs with the addition of 7.5%, where the P4 value was 3.46% lower than the P1 value with a value of 8.62%. From the research it was concluded that the addition of 5% of the molasses was the best level with a protein content of 4.29%, a fat content of 2.72%, a moisture content of 33.27%, a cooking loss of 0.83% and a yield of 2.02%Kata kunci: Chicken meatballs, Cooking loss, Kelakai, Physicochemical properties, Yield content